Geology of the Elisenheim area, Windhoek district, South West Africa, with special reference to the Matchless amphibolite belt - Finnemore, S H (Rhodes University, Faculty of Science, Department of Geology, 1976)
The Elisenheim area is situated just north of Windhoek within the Windhoek Formation of the Swakop Subgroup and is underlain by monotonous succession of semi-pelitic schists with intercalations of amphibolite, talc schist, graphitic schist and marble. Petrographic studies on units of the Matchless amphibolite which outcrop in the south of the property, have resulted in the recognition of three different types of amphibolite, namely, epidote amphibolite, porphyroblastic amphibolite and chlorite-amphibole schist. Amphibole porphyroblasts generally display patchy and zonal intergrowths of hornblende and actinolite which are indicative of non-equilibration during prograde metamorphism. Talc schists have been mapped in the north of the property. All lithotypes have undergone three phases of deformation (Fl, FZ, F3) which terminated with the faulting which underlies the Klein Windhoek, Dobra, Tigenschlücht and Kuruma rivers. Medium grade regional metamorphism accompanied F 1, F Z and F 3 and outlasted the latter. Mineral assemblages throughout the area are those of the amphibolite facies and P, T conditions prevailing during metamorphism are estimated to have been at least 5 kb at ~ 550Â° C. Petrochemical evidence indicates that the Matchless amphibolites are igneous in origin and genetically related to the ultrabasic talc schists. They are similar in composition to oceanic tholeiites and are thought to have been extruded subaqueously.
Keywords: Matchless Copper Mine (Namibia); Geology, Structural -- Namibia; Amphibolite -- Namibia; Geology -- Namibia